A future-proof past: Designing for remembering experiences. (July 2014) - van den Hoven, Elise
Personal remembering can be heavily influenced by the context in which it takes place, which includes external factors such as people, locations and things. These things can be physical, digital or a combination of both, such as digital photographs displayed on a physical screen. Together, these media and media carriers can act as memory cues, which in turn can be purposely created for the support of remembering experiences. The aim of this article is to show the challenges, potential and opportunities of this multidisciplinary research area, Materialising Memories, which creates interactive designs to be used in context. This will be illustrated through the presentation of two design case studies supporting photo sharing in everyday life: Cueb and 4Photos.